2019
DOI: 10.1155/2019/7396716
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Effect of Organotin on Thyroid Gland Function Might Contribute to Hypothyroidism

Abstract: A considerable increase in endocrine abnormalities has been reported over the last few decades worldwide. A growing exposure to endocrine-disrupting chemicals (EDCs) can be one of the causes of endocrine disorders in populations, and these disorders are not only restricted to the metabolic hormone system but can also cause abnormal functions. Thyroid hormone (TH) disruption is defined as an abnormal change in TH production, transport, function, or metabolism, which results in some degree of impairment in body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The oral administration of synthetic pyrethroid insecticide lambda-cyhalothrin to rats causes decreased T3 and T4 serum hormone concentration while increased TSH along with thyroid DNA damage suggesting primary hypothyroidism [11]. For many other chemical compounds like a biocide compound tributyltin chronic exposure causes declined T3 and T4 and elevated TSH concentrations pointing toward hypothyroidism along with many other thyroid disorders [12].…”
Section: Introductionmentioning
confidence: 99%
“…The oral administration of synthetic pyrethroid insecticide lambda-cyhalothrin to rats causes decreased T3 and T4 serum hormone concentration while increased TSH along with thyroid DNA damage suggesting primary hypothyroidism [11]. For many other chemical compounds like a biocide compound tributyltin chronic exposure causes declined T3 and T4 and elevated TSH concentrations pointing toward hypothyroidism along with many other thyroid disorders [12].…”
Section: Introductionmentioning
confidence: 99%
“…The thyroid function test is one of the most common laboratory tests usually done to investigate mood disorders. There is evidence that hypothyroidism can cause signs and symptoms of depression in humans (21). Some studies have shown increased T4 levels during the depression, while others have not shown this correlation (22).…”
Section: Introductionmentioning
confidence: 99%